Targeting melanoma metastasis and immunosuppression with a new mode of melanoma inhibitory activity (MIA) protein inhibition - Schmidt, Jennifer; Riechers, Alexander; Stoll, Raphael; Amann, Thomas; Fink, Florian; Spruss, Thilo; Gronwald, Wolfram; Koenig, Burkhard; Hellerbrand, Claus; Bosserhoff, Anja Katrin (PLoS ONE, 2012)
Melanoma is the most aggressive form of skin cancer, with fast progression and early dissemination mediated by the melanoma inhibitory activity (MIA) protein. Here, we discovered that dimerization of MIA is required for functional activity through mutagenesis of MIA which showed the correlation between dimerization and functional activity. We subsequently identified the dodecapeptide AR71, which prevents MIA dimerization and thereby acts as a MIA inhibitor. Two-dimensional nuclear magnetic resonance (NMR) spectroscopy demonstrated the binding of AR71 to the MIA dimerization domain, in agreement with in vitro and in vivo data revealing reduced cell migration, reduced formation of metastases and increased immune response after AR71 treatment. We believe AR71 is a lead structure for MIA inhibitors. More generally, inhibiting MIA dimerization is a novel therapeutic concept in melanoma therapy. © 2012 Schmidt et al.
CRIS-Team Scopus Importer:2022-08-05